The Role of Surgery in Patients with COVID-19-Related Thoracic Complications - Raveglia, Federico; Scarci, Marco; Rimessi, Arianna; Orlandi, Riccardo; Rebora, Paola; Cioffi, Ugo; Guttadauro, Angelo; Ruffini, Enrico; Benvenuti, Mauro; Cardillo, Giuseppe; Patrini, Davide; Vannucci, Fernando; et al. (Frontiers in Surgery, 2022)
Objective Patients with several thoracic complications induced by SARS-CoV-2 infection may benefit from surgery, but its role in this condition is largely unknown, and many surgeons’ advice against any surgical referrals. Our aim is to investigate the efficacy and safety of surgery in COVID-19 patients with thoracic complications requiring surgery. Methods We designed a multicenter observational study, involving nine thoracic surgery departments, evaluating patients who developed thoracic complications in hospital, surgically managed from March 1, 2020, to May 31, 2021. An overall 30-day mortality was obtained by using the Kaplan–Meier method. Multivariable Cox regression model and logistic models were applied to identify the variables associated with mortality and postoperative complications. Results Among 83 patients, 33 (40%) underwent surgery for complicated pneumothorax, 17 (20.5%) for pleural empyema, 13 (15.5%) for hemothorax, 8 (9.5%) for hemoptysis, 5 patients (6%) for lung abscess, 4 (5%) for infected pneumatoceles, and 3 (3.5%) for other causes. Within 30 days of surgery, 60 patients (72%) survived. At multivariable analysis, age (HR 1.05 [95% CI, 1.01, 1.09], p = 0.022), pulmonary hypertension (HR 3.98 [95% CI, 1.09, 14.5], p = 0.036), renal failure (HR 2.91 [95% CI, 1.19, 7.10], p-value 0.019), thoracotomy (HR 4.90 [95% CI, 1.84, 13.1], p-value 0.001) and infective affections (HR 0.17 [95% CI, 0.05, 0.58], p-value 0.004) were found to be independent prognostic risk factors for 30-day mortality. Age (OR 1.05 [95% CI, 1.01, 1.10], p = 0.023) and thoracotomy (OR 3.85 [95% CI, 1.35, 12.0] p = 0.014) became significant predictors for 30-day morbidity. Conclusion Surgical management of COVID-19-related thoracic complications is affected by high mortality and morbidity rates, but a 72% survival rate still seems to be satisfactory with a rescue intent. Younger patients without pulmonary hypertension, without renal insufficiency and undergoing surgery for infectious complications appear to have a better prognosis.